Critical Success Factors Of The Green Building Implementation In Malaysian Construction Industry - Nagarajan, Sarmila (Universiti Sains Malaysia, 2022)
The government of Malaysia introduced the concept of green building in order to achieve sustainable development goals in the construction industry. Green building plays an essential part in accomplishing the goal of sustainable development in terms of environmental protection and human well-being. According to reports, the construction business has the highest environmental impact of all industries, and one of the methods is to use green building designs and set standards to reduce energy consumption in building operations as energy efficient buildings. Green building has become more popular and significant in Malaysia, although it still does not appeal to all segments of the construction sector. While there are several benefits to society, the growth of green building continues to be hampered by various factors that appear to be impeding the implementation of green building in emerging nations such as Malaysia. Therefore, the main objective of this study to determine the factors affecting the green building implementations in Malaysian construction industry. Other than that, this study also aims to determine the success factors implementing the green building implementation. Factors affecting the implementation of green building determined have the potential to show barriers exists in the construction industry in applying green building concept while success factors analysed can create awareness among the contractors to increase the green building implementation in future buildings. From the results obtained, the social factor was perceived to be the major factor that impacts the green building implementation followed by municipal factor. The critical success factors of green building adoption in Malaysia obtained are the efficiency of green building rating tool which promotes sustainable buildings, government set an example by implementing green building concept in government buildings and trainings and higher education programme on green buildings.